Carbon Dioxide Emissions During the 2018 Kilauea Volcano Eruption Estimated Using OCO‐2 Satellite Retrievals. Issue 24 (26th December 2020) - Johnson, Matthew S.; Schwandner, Florian M.; Potter, Christopher S.; Nguyen, Hai M.; Bell, Emily; Nelson, Robert R.; Philip, Sajeev; O'Dell, Christopher W.
Abstract: This study applies Orbiting Carbon Observatory‐2 (OCO‐2) column‐averaged dry‐air mole fractions of CO2 (XCO2 ) to constrain CO2 fluxes during the 2018 Kilauea volcano eruption. CO2 enhancements (ΔXCO2 ) of 1–2 parts per million were observed far downwind of the eruption coincident with elevated sulfur dioxide (SO2 ) concentrations. The estimated CO2 emission rate was 77.1 ± 49.6 kilotons per day (kt day −1 ) on 11 July 2018 with most of the uncertainty from modeled winds and XCO2 retrievals. This emission rate is higher compared to flux estimates made with ground‐based measurements (30–40 kt day −1 ). However, cross‐sectional flux estimates made using OCO‐2 XCO2 observations will inherently be larger than ground‐based measurements near the source as these estimates comprise all sources of CO2 in the vicinity of the eruption (e.g., vegetation and soil burning). This study for the first time uses satellite XCO2 data ~200 km downwind to estimate CO2 emissions from a major volcanic eruption. Plain Language Summary: Carbon dioxide (CO2 ) is a greenhouse gas that plays a predominant role in climate change. Volcanoes emit CO2 and play a role in the global carbon cycle; however, the amount of CO2 they emit is highly uncertain. One of the main reasons for this uncertainty is the limited amount of volcanic emission measurements available to estimate these CO2 emissions. Satellites retrieving CO2 have an advantage over ground‐based measurements as they have the potential to obtain data over the entire globe. After the launch of National Aeronautics and Space Administration (NASA)'s Orbiting Carbon Observatory‐2 (OCO‐2) satellite in 2014, spaceborne observations of volcanic CO2 were possible. This study uses OCO‐2 measurements of CO2 to estimate emissions during the 2018 Kilauea volcano eruption and is the first to trace satellite CO2 data downwind from the source of a major volcanic eruption. Here we show that the Kilauea volcano eruption emitted large amounts of CO2 and OCO‐2 proved capable to observe the large atmospheric concentrations associated with these emissions. Key Points: Orbiting Carbon Observatory‐2 retrievals were applied to estimate CO2 emissions during the 2018 Kilauea volcano eruption A CO2 emission rate of 77.1 ± 49.6 kt day −1 was estimated from volcanic and other emission sources on 11 July 2018 This study is the first attempt to use satellite retrieved CO2 data far downwind of a major volcanic eruption to estimate emissions